The urgency of PKWT for employees at the notary office in view from Indonesian labor law - Violando Aloysius Teguh; Nynda Fatmawati Octarina (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to determine the urgency of PKWT for employees at a notary's office in terms of Indonesian labor law. This study uses a normative juridical legal approach. Data collection techniques in this study used documentation techniques in the form of scientific journal articles related to PKWT for employees at the notary's office in terms of Indonesian labor law. The data analysis technique used in this study is an analytical descriptive data analysis technique for PKWT juridical studies applied in a notary's office based on Indonesian labor law. The results of this study indicate that the urgency of PKWT for employees at a notary's office in terms of labor law in Indonesia is based on Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021; PKWT must be made in writing (Article 57 paragraph (1) of Law No. Job Creation Law), PKWT drawn up in writing by a notary and its employees must be registered with the Manpower Office in the area where the notary's office is located (Article 14 paragraph (1) and (2) PP No. 35 of 2021).